Single-cell sequencing of peripheral blood mononuclear cells reveals immune landscape of monkeypox patients with HIV - Yamin Liu; Xinhua Liu; Jingjing Wang; Ying Xie; Jing Guo; Zhiqiang Liu; Ying Li; Bei Jiang; Jingya Wang (Emerging Microbes and Infections)
The monkeypox (MPXV) outbreak in 2022 is more prevalent among individuals with human immunodeficiency virus (HIV). While it is plausible that HIV-induced immunosuppression could result in a more severe progression, the exact mechanisms remain undetermined. To better understand the immunopathology of MPXV in patients with and without HIV infection, we employed single-cell RNA sequencing (scRNA-seq) to analyse peripheral blood mononuclear cells (PBMCs) from six patients hospitalized for MPXV, three of whom had HIV infection (HIV antibody positive and HIV RNA level below the detection limit), and three patients only infected with MPXV (HIV-). We map the peripheral immune response in both the acute phase and the recovery period, showing the reconfiguration of peripheral immune cell phenotypes in acute stage compared with recovery stage, characterized by disturbed cell subsets and intense cell interactions mediated by monocytes and neutrophils. Importantly, we also found obviously dysregulated gene expression and cell subsets in HIV+ patients proposing mechanism underlying their serious condition. Our findings provide a comprehensive cell atlas of MPXV patients, shed light on the mechanisms underlying the severe disease progression and longer recovery time in HIV+ individuals.